Hubungan Kematangan Emosi Dengan Penyesuaian Diri Pada Pasutri Yang Tinggal Bersama Orang Tua Di Kecamatan Megang Sakti Musirawas - Umi Khoiriyah; Eko Oktapiya Hadinata (Indonesian Journal of Behavioral Studies, 2021)
This study aims to determine the relationship between emotional maturity and self- adjustment in couples living with parents in Megang Sakti Musi Rawas District. This research is a quantitative research using a correlational research design. The sampling technique in this study was using the Purposiv Sampling technique as many as 40 couples who lived with their parents in Megang Sakti District. Data were collected using a Likert scale, interviews, observations, and documentation. Hypothesis testing in this study uses simple regression analysis. The value of sig.0,000 and r square of 0.850 shows that emotional maturity has a contribution of (85%) while the rest is influenced by other variables not discussed in this study. While the value of r is 0.922, this shows that the higher a person's emotional maturity, the higher the adjustment of a couple living with their parents in Megang Sakti Musi Rawas District.